Optimalisasi Peran Pimpinan Pesantren dalam Pengelolaan Organisasi Santri di Pesantren Terpadu Aceh - Suwardy, Dadang Chaidir; Iskandar, Iskandar; Bahri, Saiful (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2024)
This study aims to analyze the factors influencing the success of student organization management in Pesantren Terpadu Al-Muslim and Pesantren Modern Al-Zahrah. The primary focus is to identify the elements supporting the success of student organizations, including the selection of human resources, organizational environment, and collaboration among members. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation involving mentors, organization administrators, and pesantren leaders. The findings reveal that the success of student organization management is influenced by four key factors. First, the quality of human resources selected through a competency-based process emphasizing spiritual, academic, and managerial capabilities. Second, a supportive organizational environment, such as regular motivation and the freedom to develop new ideas. Third, strong collaboration among organization members facilitated by effective communication. Fourth, leadership that fosters synergy and shared values within the organization. The implications of this study indicate that effective student organization management requires a combination of qualified administrator selection, the creation of a conducive working environment, and synergy among organization members. These findings contribute to the development of student organization management strategies in pesantren and serve as a reference for other Islamic educational institutions in enhancing the effectiveness of student organizations.